2022
DOI: 10.2903/j.efsa.2022.7074
|View full text |Cite
|
Sign up to set email alerts
|

Tolerable upper intake level for dietary sugars

Abstract: Following a request from five European Nordic countries, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was tasked to provide scientific advice on a tolerable upper intake level (UL) or a safe level of intake for dietary (total/added/free) sugars based on available data on chronic metabolic diseases, pregnancy‐related endpoints and dental caries. Specific sugar types (fructose) and sources of sugars were also addressed. The intake of dietary sugars is a well‐established hazard in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 333 publications
(689 reference statements)
3
34
0
1
Order By: Relevance
“…The 4–6% of the energy in a recommended diet that may be used on EDNP food and drinks is consistent with the WHO’s recommendation and the EFSA’s opinion on dietary sugars, emphasizing the additional health benefits of reducing the intake of free sugar to less than 5% or as low as possible of the total energy intake [ 31 , 32 ]. Recently, the 2020 Dietary Guidelines Advisory Committee has suggested that less than 6% energy from added sugars is more compatible with a dietary pattern that is nutritionally adequate [ 3 ].…”
Section: Discussionsupporting
confidence: 57%
“…The 4–6% of the energy in a recommended diet that may be used on EDNP food and drinks is consistent with the WHO’s recommendation and the EFSA’s opinion on dietary sugars, emphasizing the additional health benefits of reducing the intake of free sugar to less than 5% or as low as possible of the total energy intake [ 31 , 32 ]. Recently, the 2020 Dietary Guidelines Advisory Committee has suggested that less than 6% energy from added sugars is more compatible with a dietary pattern that is nutritionally adequate [ 3 ].…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, for some age classes, the proposed SPSs could be deemed very small, limiting the acceptance of recommendations by parents. In addition to that, the strong restriction of sweet products following the recommendations limit of added sugars ( 24 , 83 , 84 ) exacerbated the monotony of food choices, especially for breakfast and snacks that in some cases could appear as difficult application and even with the inclusion of “discretionary foods” for children more than that was recommended for adults ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the WHO updated dietary guidelines pertinent to sugar intake and recommended decreasing the intake of FS to less than 10% EI as a ‘strong recommendation’ [ 7 ], and to less than 5% as a conditional recommendation [ 7 ]. The Scientific Advisory Council on Nutrition in England adopted a relatively similar approach, providing a recommendation of 10% of calories from AS, with the ultimate goal of achieving an even lower intake of 5% [ 23 ]. The American Heart Association has called for even stricter restrictions on calories from AS, with a proposed upper limit of no more than 150 kcal per day for the average adult man and no more than 100 kcal of AS per day for the average adult woman [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%